Pengaruh Komitmen Organisasi Dan Gaya Kepemimpinan Terhadap Turnover Intention Karyawan (Studi Pada Coffee Shop Kopi Studio24 Kota Malang) (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis study aims to determine the effect of organizational commitment and leadership style on turnover intention in Coffee Shop Kopi Studio24. This research was conducted in Malang City which included 48 employees and several managers as respondents. This study uses a type of survey research that all employees can be sampled. The analytical method used in this study is multiple linear regression analysis with hypothesis testing using t test and f test and processed using SPSS 16.0 to analyze several hypotheses.The results of this study indicate that Organizational Commitment has no effect on turnover Intention. Leadership style has a significant effect on turnover intention.Keywords: Organizational Commitment, leadership style and Turnover Intention